2017
DOI: 10.18632/oncotarget.17016
|View full text |Cite
|
Sign up to set email alerts
|

Driver genes in non-small cell lung cancer: Characteristics, detection methods, and targeted therapies

Abstract: Lung cancer is one of the most common causes of cancer-related death in the world. The large number of lung cancer cases is non-small cell lung cancer (NSCLC), which approximately accounting for 75% of lung cancer. Over the past years, our comprehensive knowledge about the molecular biology of NSCLC has been rapidly enriching, which has promoted the discovery of driver genes in NSCLC and directed FDA-approved targeted therapies. Of course, the targeted therapies based on driver genes provide a more exact optio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 86 publications
(87 reference statements)
1
57
0
Order By: Relevance
“…We identified that IGF2BP2 rs4402960 T allele might probably be a protective factor for NSCLC, which was not consistent with the findings of previous studies. It is believed that there are some LC-related driver genes possessing low frequency variant, which modify the states of chromatin or DNA 37. In addition, intronic region could bind to some proteins and even directly alter special gene transcription 3739.…”
Section: Discussionmentioning
confidence: 99%
“…We identified that IGF2BP2 rs4402960 T allele might probably be a protective factor for NSCLC, which was not consistent with the findings of previous studies. It is believed that there are some LC-related driver genes possessing low frequency variant, which modify the states of chromatin or DNA 37. In addition, intronic region could bind to some proteins and even directly alter special gene transcription 3739.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, these TK inhibitors generate high response rates and significant survival benefits in tumors carrying a somatic mutation in the TK receptor targeted by the TK inhibitor. The identification of actionable driver mutations in these receptors, including EGFR , ALK , ROS , BRAF and ERBB2 mutations, combined with the decreasing cost of genomic testing was key for the clinical implementation of these treatments . However, all NSCLC tumors at some point acquire resistance to these treatments.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of actionable driver mutations in these receptors, including EGFR, ALK, ROS, BRAF and ERBB2 mutations, combined with the decreasing cost of genomic testing was key for the clinical implementation of these treatments. 10 However, all NSCLC tumors at some point acquire resistance to these treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Non‐small cell lung cancer (NSCLC) accounts for over 85% of lung cancer diagnoses and most patients present with advanced stage at the time of diagnosis . Current standard first‐line treatment for advanced NSCLC is platinum‐based doublet chemotherapy when no targetable alterations, such as EGFR mutations or ALK or ROS1 rearrangements, are detected in genomic testing .…”
Section: Introductionmentioning
confidence: 99%